KREATIVITAS KAHARUDDIN DEA IMOK DALAM KARYA TARI KEMANG PASIKI KECAMATAN ALAS KABUPATEN SUMBAWA - eka Nurhayati; Silvester Pamardi (Greget, 2019)
The Kemang Pasiki Dance was created in 2016 by Kaharuddin Dea Imok, who originated from his interest in seeing the skills of Sumbawa women. The problem is formulated in this research the first how to form Kemang Pasiki dance second how to creativity Kaharuddin Dea Imok in creating the Kemang Pasiki dance. Based on the object examined, this research uses a qualitative method describing the research object according to the data in the field in the form of real data. To know about the form of dance Kemang Pasiki researchers use the concept of Suzanne K, the writer that is made clear by the opinions of Soedarsono discussing about dance elements that include motion, floor patterns, music, fashion makeup and place Show. Next to discuss about the creativity of Kaharuddin Dea Imok use the thought concept of Mel Rodes, and for the process used 4P namely pribadi (person), pendorong (press), Proses (prosess) and produk (product). The results of the study gained that creativity Kaharuddin Dea Imok can be seen from the experience as a choreographer in creating dance works. Kemang Pasiki Dance forms can be seen Composition of the elements of the movement, the floor pattern, and the Music, fashion makeup and a place of performances that become one unit In the Kemang Pasiki dance performance. Creativity Imok can be seen from the development of the basic movements of Sumbawa dance, and movements that are calculated with the Rdat motion and the Zapin motion and the skills movement of Sumbawa women.Keyword: Kemang Pasiki dance, dance form, and creativity.